THE INFLUENCE OF E-SERVICE QUALITY AND DIGITAL CUSTOMER SATISFACTION ON USER GROWTH (POLITEKNIK LP3I JAKARTA, 2026)
The integration of Financial Technology (Fintech) within non-bank financial industries challenges traditional collateral-based lending institutions to optimize their digital consumer touchpoints. This study investigates the empirical impact of E-Service Quality (X1) and Digital Customer Satisfaction (X2) on User Growth (Y) at PT Indogadai Prima, Tangerang Branch, an enterprise that suffered a severe decline in monthly active users throughout the second semester of 2025. A quantitative descriptive approach was adopted for this research. By utilizing the Slovin formula, a sample size of 56 digital consumers was selected via simple random sampling from a known population of 65 active users . Primary data were gathered through web-based structured questionnaires using a 5-point Likert scale . Data analysis was conducted via multiple linear regression analysis using IBM SPSS . The analytical results reveal that E-Service Quality and Digital Customer Satisfaction function as critical drivers that significantly mitigate user churn and trigger positive user acquisition rates . Micro-finance institutions must scale up their digital infrastructure by implementing automated valuation algorithms and open API omnichannel payment gateways to sustain market relevance within competitive digital business networks.